A highly selective and efficient method for the production of 5-hydroxymethylfurfural from dehydration of fructose using SACS/DES catalytic system. (15th June 2019) - Tran, Phuong Hoang; Tran, Phuong Vy
Highlights: SACS/DES1 is cheaper, eco-friendlier, and efficient catalytic system. The HMF was obtained in 67% yield and 100% selectivity. The simple isolation of HMF from DES was performed by phase extraction. SACS/DES1 could be recycled with a little decrease in reactivity. Abstract: Our findings could have an impact on the synthesis of HMF and the rational design of deep eutectic solvents (DES) for liquid‐phase separations of HMF in biomass processing. Brønsted acidic sites in the case of sulfonated amorphous carbon–silica (SACS) led to excellent selectivity in the dehydration of fructose in deep eutectic solvents. The deep eutectic solvents were found to play a crucial role to suppress the formation of undesired products and make the work-up separation of HMF easier. The combination of amorphous carbon with deep eutectic solvent allowed to conduct a transformation of fructose to HMF with 67% yield and 100% selectivity towards HMF at 110 °C in 4 h. The excellent selectivity, work-up simplification, and recyclable catalytic system provide a cost-effective strategy for the synthesis of HMF.